Peruvian Nonprofit Journalism: IDL- Reporters - Requejo Alemán, José Luis (2022)
The purpose of this article is to register the pregnancy and birth of IDL-Reporters, the first initiative of nonprofit investigative journalism born in Peru. As business idea, IDL-Reporters share same foundational strengths and weaknesses as its european and U.S. peers, although with more difficulty for finding financial sources and make an impact on traditional media, due to political and commercial context.